De-embedding techniques for characterizing high frequency noise in nanometre CMOS devices - Loo, Xi Sung. (2012)
Aggressive scaling of CMOS devices over the past decades has enabled System-on-Chip (SoC) solution which permits full integration of digital circuits with analog and RF functions in one chip at low cost. However, the growing complexity of radio frequency integrated circuits requires accurate characterization of CMOS device for successful modelling and IC design.